Draft 12th Five Year Plan (2012-17) and Annual Plan (2012-2013) Part-III (Statements) Government of Tripura - Planning Commission (Planning Commission, 2012)
Sector wise Draft 12th Five Year Plan (2012-17) and Annual Plan (2012-13) Proposed Outlays, Draft 12th Five Year Plan (2012-17) and Annual plan (2012-13) Proposed Outlays (Scheme-wise), Physical Targets and Achievements, Statement Regarding Externally Aided Projects, Centrally Sponsored Schemes, Financial Outlays : Proposals for Tribal Sub-Plan (TSP), Physical Targets and Achievements: Proposals for Tribal Sub-Plan (SCSP), Physical Targets and Achievements: Proposals for Scheduled Castes Sub-Plan (SCSP), Financial Outlays / expenditure for Voluntary Sector.
Planning (P and C) Department, Government of Tripura
Planning (P and C) Department, Government of Tripura